2004
DOI: 10.1038/nature02465
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence and analysis of human chromosome 9

Abstract: Chromosome 9 is highly structurally polymorphic. It contains the largest autosomal block of heterochromatin, which is heteromorphic in 6-8% of humans, whereas pericentric inversions occur in more than 1% of the population. The finished euchromatic sequence of chromosome 9 comprises 109,044,351 base pairs and represents >99.6% of the region. Analysis of the sequence reveals many intra- and interchromosomal duplications, including segmental duplications adjacent to both the centromere and the large heterochromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(79 citation statements)
references
References 52 publications
3
75
0
1
Order By: Relevance
“…This band is known to be involved in constitutional pericentric inversions of chromosome 9, which occurs with a frequency of about 2% in the general population (37). Additionally, this region is known to be breakpoint prone and carries segmental duplications (38). Our own studies showed that the constitutional pericentric inversions of chromosome 9 are not due to one or two founder mutations but that they differ on a molecular level (8,39; our own unpublished data).…”
Section: Alignment Of Breakpoints With Segmental Duplicationsmentioning
confidence: 99%
“…This band is known to be involved in constitutional pericentric inversions of chromosome 9, which occurs with a frequency of about 2% in the general population (37). Additionally, this region is known to be breakpoint prone and carries segmental duplications (38). Our own studies showed that the constitutional pericentric inversions of chromosome 9 are not due to one or two founder mutations but that they differ on a molecular level (8,39; our own unpublished data).…”
Section: Alignment Of Breakpoints With Segmental Duplicationsmentioning
confidence: 99%
“…Interestingly, chromosome 9, which is orthologous to large parts of the chicken Z, is highly structurally polymorphic in humans (Humphray et al, 2004). Trisomies of human 9p (Wilson et al, 1985), and monosomies of 5q and 18q (which all share homology with the chicken Z), survive to birth (Nusbaum et al, 2005;Boultwood et al, 2010).…”
Section: Does Dosage Insensitivity Predispose An Autosome To Evolve Smentioning
confidence: 99%
“…1 Human ATGL (also called PNPLA2 or PLPL2) encodes adipose triglyceride lipase (ATGL, also known as desnutrin or PNPLA2) and is localizedPNPLA4 (PLPL4, X chromosome); 5 PNPLA6 (PLPL6 or NTE) (neuropathy target esterase, chromosome 19); 6,7 PNPLA7 (PLPL7, chromosome 9); 8 and PNPLA8 (PLPL8 or IPLA2G, calcium-independent phospholipase A2-gamma, chromosome 7). [9][10][11] ATGL catalyzes the first step in the hydrolysis of triglycerides in adipocytes and lipid droplets in other tissues of the body, and also acts as an acylglycerol transacylase.…”
Section: Introductionmentioning
confidence: 99%